The Australian Twins Economic Preferences Survey. (17th December 2021) - Kettlewell, Nathan; Tymula, Agnieszka
Abstract: This article describes the Australian Twins Economic Preferences Survey (ATEPS). The data set comprises a wide variety of preference and behavioral measures (risk aversion, impatience, ambiguity aversion, trust, confidence) elicited using incentivized decision tasks. One-thousand one-hundred twenty Australian adult twins (560 pairs) completed the survey, making it one of the largest data sets containing incentivized preference measures of twins. As the survey was conducted during the COVID-19 pandemic, we also collected information on experiences related to the pandemic, along with a variety of questions on political attitudes and mental wellbeing. We hope that ATEPS can make a valuable contribution to social science and genetics research.